2012
DOI: 10.1016/j.immuni.2012.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Inborn Errors of Human JAKs and STATs

Abstract: Inborn errors of the genes encoding two of the four human JAKs (JAK3 and TYK2) and three of the six human STATs (STAT1, STAT3, and STAT5B) have been described. We review the disorders arising from mutations in these five genes, highlighting the way in which the molecular and cellular pathogenesis of these conditions has been clarified by the discovery of inborn errors of cytokines, hormones, and their receptors, including those interacting with JAKs and STATs. The phenotypic similarities between mice and human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
265
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 294 publications
(272 citation statements)
references
References 148 publications
2
265
0
5
Order By: Relevance
“…The basis for the small increased transcriptional activity and, presumably, the partial oncogenic capacity of STAT3C (as the mutant was named) was a more avid DNA binding of the STAT3C mutant leading to a slower off time from DNA than wild type and a concomitant slower dephosphorylation rate. Most recently human mutations, both positive-and negative-acting in STATs 1 and 3 (21,(27)(28)(29)(30)(31), have been reported especially in the SH2 domain, some of which have constitutive activity (31).…”
Section: Stat3 | Linker Domain | Mutantsmentioning
confidence: 99%
“…The basis for the small increased transcriptional activity and, presumably, the partial oncogenic capacity of STAT3C (as the mutant was named) was a more avid DNA binding of the STAT3C mutant leading to a slower off time from DNA than wild type and a concomitant slower dephosphorylation rate. Most recently human mutations, both positive-and negative-acting in STATs 1 and 3 (21,(27)(28)(29)(30)(31), have been reported especially in the SH2 domain, some of which have constitutive activity (31).…”
Section: Stat3 | Linker Domain | Mutantsmentioning
confidence: 99%
“…This suggested that the wild-type residues would contribute to formation and stabilization of the antiparallel dimer and help to facilitate the subsequent Tyr-701 dephosphorylation process. In fact, in addition to the GOF residues of the CCD, the DBD residues facing the ␣3 helix of the dimeric counterpart, such as Gly-384, Thr-385, and Lys-388, were also frequently identified as CMC pathogenic mutations (3,4). Hence, missense mutations substituting Gln-275 or Glu-282, which were newly identified in this report as GOF residues and that surrounded the interface of the anti-parallel dimer, could give a high risk for onset and development of CMC disease.…”
Section: Discussionmentioning
confidence: 99%
“…Recent progress in the methodologies of genome sequencing has revealed a wide variety of single nucleotide polymorphisms in the STAT1 gene locus (3,4). These mutations frequently change the resultant STAT1 amino acid sequence but rarely generate critical damage to its immunoregulatory functions.…”
mentioning
confidence: 99%
“…JAK activation leads to phosphorylation of the receptor and recruitment of STAT family transcription factors, which are then phosphorylated by the JAK and translocated to the nucleus where they induce gene transcription. The JAK family consists of four members (JAK1, JAK2, JAK3, and tyrosine kinase 2 or TYK2), each of which binds a distinct set of cytokine receptor subtypes and hence has a unique gene knockout phenotype, ranging from embryonic lethality due to neuronal and erythropoietic defects (JAK1 and JAK2, respectively) (3)(4)(5), to profound immune system deficiencies (JAK3 and TYK2) (6).…”
Section: Jak1 | Jak3mentioning
confidence: 99%